A 17-mer Membrane-Active MSI-78 Derivative with Improved Selectivity toward Bacterial Cells - Claudia Monteiro (2015)
Antimicrobial peptides are widely recognized as an excellent alternative to conventional antibiotics. MSI-78, a highly effective and broad spectrum AMP, is one of the most promising AMPs for clinical application. In this study, we have designed shorter derivatives of MSI-78 with the aim of improving selectivity while maintaining antimicrobial activity. Shorter 17-mer derivatives were created by truncating MSI-78 at the N- and/or C-termini, while spanning MSI-78 sequence. Despite the truncations made, we found a 17-mer peptide, MSI-78(4-20) (KFLKKAKKFGKAFVKIL), which was demonstrated to be as effective as MSI-78 against the Gram-positive Staphylococcus strains tested and the Gram-negative Pseudomonas aeruginosa. This shorter derivative is more selective toward bacterial cells as it was less toxic to erythrocytes than MSI-78, representing an improved version of the lead peptide. Biophysical studies support a mechanism of action for MSI-78(4-20) based on the disruption of the bacterial membrane permeability barrier, which in turn leads to loss of membrane integrity and ultimately to cell death. These features point to a mechanism of action similar to the one described for the lead peptide MSI-78.